1994
DOI: 10.1159/000109556
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in the Control of the Estrous Cycle of the Indian Desert Gerbil <i>(Meriones hurrianae: </i>Jerdon)

Abstract: Daily administration of melatonin for 8 weeks, either in the morning (9 a.m.) or late in the afternoon (5 p.m.), resulted in significant prolongation of the estrous cycle in the Indian desert gerbil Meriones hurrianae. The gonadosomatic index increased significantly (p < 0.01) in the melatonin-treated gerbils compared to the control animals. Histological study of the ovaries revealed enlargement of follicles and corpora lutea with hypertrophied granulosa cells in the melatonin-treated gerbils in comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Melatonin, which is considered to be a chief hormonal product of the pineal gland, has a broad spectrum of physiological actions [3] which include thermoregulation [4,5], reproduction [1,6,7], intermediary metabolism [8], electrolyte metabolism [9], blood flow and evaporative water loss during heat stress in rats [10]. Melatonin is also implicated in immune response [11] and oncostatic action [12], Recent studies reveal that melatonin-induced release of opioid peptides mediate immunoenhancing effects [13], Ear lier studies from our laboratory indicated in volvement of melatonin in hemopoiesis and its rhythms [14].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin, which is considered to be a chief hormonal product of the pineal gland, has a broad spectrum of physiological actions [3] which include thermoregulation [4,5], reproduction [1,6,7], intermediary metabolism [8], electrolyte metabolism [9], blood flow and evaporative water loss during heat stress in rats [10]. Melatonin is also implicated in immune response [11] and oncostatic action [12], Recent studies reveal that melatonin-induced release of opioid peptides mediate immunoenhancing effects [13], Ear lier studies from our laboratory indicated in volvement of melatonin in hemopoiesis and its rhythms [14].…”
Section: Introductionmentioning
confidence: 99%